Positive Effects of SIBI Alphabet Cards on Increasing Vocabulary Acquisition in Children with Special Needs Deaf - Fatichatul Istiqomah; Luluk Sri Agus Prasetyoningsih; Ari Ambarwati; Sri Wahyuni (STAI Hubbulwathan Duri, 2023)
Children with Special Needs with hearing impairment have hearing loss, classified as deaf and hard of hearing. Hearing loss in children with special needs is associated with long-term academic and communication difficulties, so it will hinder the learning process and potentially experience obstacles in developing students' thinking or cognitive quality. This study aims to analyze the effect of Indonesian language learning media using the SIBI Alphabet Card on increasing vocabulary acquisition in children with hearing impairment. This research is true experimental research with the randomized three-group pretest-posttest only design. A total of 27 children with hearing impairment, categories slight, moderate, profound, male and female, aged 8-22 years. Subjects were randomly divided into three study groups, namely G1 (n = 10; Slight Deaf), G2 (n = 8; Moderate Deaf), G3 (n = 9; Profound Deaf). The Indonesian-language learning media intervention using the SIBI Alphabet Card was carried out 2x/week for four weeks. Data were collected before and after the intervention using a written test instrument. The data analysis technique used the Paired Samples T-Test test with the Packet for Social Science (SPSS) Statistics Software version 21. Based on the results of the study showed that there was an increase in vocabulary acquisition in the three groups before and after the intervention (p0.001). In general, concluded that the provision of Indonesian-language learning media using the SIBI Alphabet Card which is carried out two times/week for four weeks is effective in increasing vocabulary acquisition in deaf children with special needs.